+0  
 
0
100
1
avatar

If (x, y ) is a solution to the system of equations \(xy=6 \) and \(x^2y + xy^2 + x + y = 63\), find \(x^2 + y^2\)

 Jun 14, 2021
 #1
avatar+121063 
+1

xy  =   6

x^2 y + xy^2   +  x + y  =  63    ⇒    xy  ( x + y)  +  x + y  =  63   ⇒   (x + y) (xy + 1)  =  63

 

So

 

(x + y)  ( 6 + 1)   =  63

 

(x + y)  * 7   =  63

 

x+ y   = 63  / 7

 

x + y  =  9              square both sides

 

x^2  +  2xy + y^2  =  81

 

x^2  + y^2  + 2(6)  =  81

 

x^2  + y^2   + 12   =  81

 

x^2  +  y^2   = 81  - 12

 

x^2  + y^2   =  69

 

 

cool cool cool

 Jun 14, 2021

44 Online Users

avatar
avatar